LOADS TRANSMITED TO THE METALLIC TOWERS OF THE EXTRACTING INSTALLATIONS IN THE CASE OF THE APPLICATION OF THE SAFETY BRAKE - Razvan Itu; Alexandru Ioan Pop (Fiabilitate şi Durabilitate)
In the paper there are presented certain aspects concerning the determination of loads transmitted through the bearings of the extracting pulleys of the structure of the metallic towers of the extracting installations In the case of the application of the safety brake The exemplification of the determination of the loads transmitted to the metallic tower in the case of the application of the emergency brake has been done by taking into study the extracting installation ,, Auxiliary well No.12”, from Lupeni Mining Plant. The extracting installation is unbalanced. The wrapping organ of the installation machine is a double wheel with the wrapping of the extracting cable in one layer. The extracting vessels are untipping cages with two levels, with two trolleys per level. The drive of the installation‟s machine is asynchronous, the machine‟ s reducer having two drives.